(untitled) (Palimpsesto, 2025)
Social studies of disability and social studies of care have pursued their research in parallel, although they overlap at various points. This article aims to reconstruct and analyze the debates surrounding care received and care provided in both fields of research. A bibliographical and theoretical review of national and international organizations will be conducted. The results indicate tensions surrounding autonomy and women with disabilities as subjects of feminism, and a rapprochement regarding the recognition of the vulnerabilities and interdependencies that constitute human relationships.